The Ethical Sensitivity of Nurses in Turkey - Ersoy, Nermin (Nursing ethics, 2001)
In this study we tried to gain information about the ethical sensitivity (as well as the ethical knowledge) of nurses working at the bedside in our country. Four scenarios were presented to 165 nurses working in hospital wards in Kocaeli. More than half of the nurses can be considered to have made decisions based on beneficence for the first scenario, while more than half of them preferred to make decisions based on autonomy for the second and the fourth scenarios. For the third scenario, most of the nurses (76.4%) can be said to have based their decisions on veracity. These results suggest that these nurses were sensitive to issues of confidentiality, truth telling and beneficence; however, they were not equally sensitive when the right to refuse treatment was concerned.